Gernikaren itzalpean: Propaganda, Appropriation, and Depoliticisation of Basque Art Music - Besada, José; Zubizarreta, Ainara (Circuit, 2018)
The Bombing of Guernica stands as the best-known war crime during the Spanish Civil War. The town symbolically representing the Basque essences was destroyed by a German-Italian air raid lasting over three hours, and almost two hundred people were killed. Unfortunately, this abominable event remains contentious among disparate political factions, sometimes upholding its memory by means of tailor-made interpretations.As music often performs a political role within conflicts, particularly those involving violence, it is not surprising that the Bombing of Guernica has inspired several compositions of art music. Among them, we study three works by Basque composers, namely Pablo Sorozábal, Francisco Escudero, and Ramon Lazkano. Each case study respectively stands, politically speaking, as a propagandistic event, a musical appropriation, and a collateral depoliticization of the vivid memories around the war crime.